Pengaruh Kecerdasan Emosional Dan Self-regulated learning Dalam Mengembangkan Keterampilan Berpikir Kritis Siswa Pada Mata Pelajaran Ekonomi - Ardianto, Radhika; Hermawan, Yoni; Gumilar, Gugum (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
The problem in this study is the low critical thinking skills possessed by students in economic subjects. This study aims to determine the effect of emotional intelligence and self-regulated learning in developing students' critical thinking skills in economics subjects. This study uses a quantitative approach with a survey method. The study population amounted to 178 students with a sample size of 123 students in class XI IPS SMA Negeri 1 Ciamis in the 2024/2025 school year, with sampling using proportionate sampling technique. The results showed that: (1) emotional intelligence has a positive and significant effect on critical thinking skills; (2) self-regulated learning has a positive and significant effect on critical thinking skills; (3) emotional intelligence and self-regulated learning simultaneously have a positive and significant effect on critical thinking skills by obtaining a coefficient of determination (R2) of 0.672. This means that the contribution of the independent variables to critical thinking skills is 67.2% and the remaining 32.8% is influenced by other variables outside this study.